2016
DOI: 10.1111/aos.13120
|View full text |Cite
|
Sign up to set email alerts
|

Cataract surgery in patients with neovascular age‐related macular degeneration

Abstract: Cataract surgery improves vision in patients undergoing treatment for neovascular AMD. Cataract surgery was not associated with an increased need for anti-VEGF treatment and patients who were in active anti-VEGF treatment had better visual outcomes than patients who had cataract surgery after long injection-free periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 18 publications
4
20
0
Order By: Relevance
“…Concern has been raised that cataract surgery may increase the risk of progression of neovascular AMD (Kessel et al. ; Park et al. ,b; Wang et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concern has been raised that cataract surgery may increase the risk of progression of neovascular AMD (Kessel et al. ; Park et al. ,b; Wang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Cataracts and neovascular AMD are two leading causes of visual impairment and blindness worldwide, often present concurrently in older persons (Congdon et al 2004;Qian & Young 2014). Concern has been raised that cataract surgery may increase the risk of progression of neovascular AMD (Kessel et al 2016;Park et al 2016a,b;Wang et al 2016). Moreover, cataract surgery and neovascular AMD share common risk factors, such as increasing age, smoking and cardiovascular disease, as well as occur concurrently in many cases (Klein et al 1998;Wang et al 1999;Tabandeh et al 2012;Hu et al 2017).The presence of neovascular AMD is a documented risk factor for poor visual outcomes after cataract surgery (Lundqvist & M€ onestam 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Patients are operated at better preoperative visual acuities . After publication of the guideline, a large retrospective study with prolonged follow-up demonstrated that cataract surgery in patients with exudative AMD is visually beneficial and does not increase the need for anti-VEGF injections (Kessel et al 2016d). In Copenhagen, 30% of patients referred from private practice to cataract surgery at a university clinic did not proceed to have surgery (Kessel et al 2016c).…”
Section: Discussionmentioning
confidence: 99%
“…Cataract surgery in patients with AMD was also not covered as an item in the questionnaire because it was too difficult to formulate questions that would give a reliable indication on which criteria would lead to cataract surgery for the same reasons as stated above. After publication of the guideline, a large retrospective study with prolonged follow-up demonstrated that cataract surgery in patients with exudative AMD is visually beneficial and does not increase the need for anti-VEGF injections (Kessel et al 2016d). This finding supports the results of our meta-analysis of epidemiologic studies which showed that the risk of incident AMD or progression of AMD was approximately the same in patients with un-operated cataract and operated cataracts (Kessel et al 2015c), suggesting that it is not cataract surgery in itself that is the risk factor but rather common risk factors for cataract and AMD, for example smoking (Kelly et al 2005;Cong et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The studies published about cataract surgery in patients with neovascular AMD are mainly retrospective, FAG was only performed as a diagnostic test and not on the follow-up; some of them without control group and with short periods of follow-up [15,16,[25][26][27][39][40][41][42][43][50][51][52][53][54][55]58]. In addition, the protocols used in the reported studies, were inhomogeneous (treat and extend, pro-re-nata and monthly injections), but none compared these protocols between them, or even between different anti-VEGF agents (bevacizumab, ranibizumab or aflibercept) [38,39,[41][42][43][52][53][54][55].…”
Section: Neovascular Amdmentioning
confidence: 99%